The scenography of Howard Barker : The Wrestling School aesthetic 1998-2011 - Kipp, Lara Maleen (London: Routledge, 2021)
"Influential contemporary British playwright and director Howard Barker has been engaging with the scenography of The Wrestling School's productions since 1998. Despite this active involvement in the design of set, costume, lighting and sound, no in-depth published study on this aspect of his work exists to date. This monograph therefore offers the first comprehensive and detailed analysis of Barker's scenographic practice. Combining aesthetic analysis of play texts and production records with original interview materials, this book presents the first full-length foray into Barker's scenography. It features extracts from conversations with designers working with Barker, and with Barker himself. In addition, it presents the first printed versions of select set and costume designs by Barker. With the first fully detailed analysis of Barker's scenographic work, this book will be a vital read for scholars and postgraduates of Barker Studies, contemporary British and European Drama, Theatre, and Scenography"--
Includes bibliographical references and index.
Keywords: Theaters